A Schiff base 4-chloro-2-((pyridin-3-ylimino)methyl)phenol: crystal structure details, computational study, proteolytic properties, molecular docking, in vivo toxicity and in vitro antibacterial activity - Sharov, A.V.; Nikolaychuk, P.A.; Tereshkina, A.A.; Dostovalova, A.V.; Enova, Y.A.; Popova, D.S.; Rychkova, D.A.; Kurochkina, A.Y.; Savinova, V.V.; Nakoskin, A.N.; Shipitsyna, I.V.; Filisteev, O.V.; et al. (International Journal of Biology and Chemistry, 2025)
In the present study, a synthesis, computational modeling and experimental investigation of 4-chloro-2-((pyridin-3-ylimino)methyl)phenol was reported. A Hirshfeld surface analysis was used for elucidation of interatomic contacts to the crystal structure of the sub-stance. A DFT analysis was used for geometry optimisation, modeling of both IR- and electronic spectra of three tautomeric forms and their comparison with the experimental spectra. A molecular docking was used for estimation of binding of three tautomeric forms with some proteins of Staphylococcus aureus and Pseudomonas aeruginosa. The ionisation constants in hydroethanolic mixtures were determined. The results of the antimicrobial tests of microamounts of 4-chloro-2-((pyridin-3-ylimino)methyl)phenol deposited onto the surface of titanium alloy of medical grade against the same microbials, and of the toxicity test of this compound with laboratory mice were provided. An inhibitory activity against Pseudomonas aeruginosa was revealed. Keywords: Schiff base; crystal structure; Hirshfeld surface analysis; computational study; DFT; molecular docking; toxicity; antibacterial activity.